Ancient Schwannoma of the Gallbladder. Issue 2 (28th February 2020) - de Bakker, J. K.; Witteveen, E.; van den Bergh, J.; Daams, F.
ABSTRACT: Schwannomas are benign tumors which arise in the Schwann cells of the peripheral nerves. They develop anywhere in the human body but are less frequent found in the digestive tract. A 67-year-old female patient was referred to our tertiary HPB department with a asymptomatic mass of the gallbladder. Contrast‐enhanced computed tomography revealed a rather homogeneous, well-circumscribed, high-density ovoid mural mass. An open cholecystectomy was performed. A final diagnosis of schwannoma with degenerative atypia, so-called "ancient schwannoma", was made. Clinical recovery and follow-up was uneventful, with no signs of recurrence.